Analysis and Evaluation of Line Different Protection Characteristics Employed in Numerical Relay - Le, Kim Hung; Vu, Phan Huan (Old Journal, 2019)
This paper describes clearly different points including advantages and disadvantages of a line differential protection relay system which uses a single slope characteristic of Siemens 7SD522, a double slope characteristic of Areva P543, Abb RED670, GE L90, and an alpha plane characteristic of SEL311L. After that, the paper selected a 220kV Buôn Kuốp – Buôn Tua Srah transmission line as an example for the relay setting calculations of these characteristics. We then perform testing the performance of the introduced relay model at various fault conditions by Matlab/Simulink software. The result shows that on internal fault the relay model has a high operating sensitivity, and fast time response whilst it remains stable on all external faults and normal condition.